Understanding school climate: the influence of peer social interactions on student resilience - Kholifah, Nur; Sylvia, Novia; Ahman, Ahman (KONSELI: Jurnal Bimbingan dan Konseling (E-Journal), 2024)
Resilience is an essential factor in individual self-development. Resilience is a distinguishing aspect of individuals facing life events that they experience as part of adaptation. This study aims to determine the relationship between peer social interaction and student resilience. The approach used is a quantitative method with a correlational design. The instruments used are peer social interaction and resilience instruments developed and tested to produce valid and reliable measurements. Data collection uses peer social interaction instruments and resilience instruments. The respondents of the study were 195 students in grades VII, VIII, and IX of Juniour High School Muhammadiyah 9 Yogyakarta. Data analysis used simple regression techniques using SPSS (Statistical Package for Social Science) version 16. The results of the hypothesis test indicate that peer social interaction has a significant positive relationship with resilience. Peer social interaction has an influence. Other variables outside of peer social interaction affect the remaining 69.6%. The novelty of this study lies in its specific focus on the context of secondary schools, especially in the Muhammadiyah school environment, which has unique cultural and social dynamics that may influence the relationship between peer interaction and resilience.